2007
DOI: 10.1302/0301-620x.89b7.18906
|View full text |Cite
|
Sign up to set email alerts
|

Compartment syndrome following ankle sprain

Abstract: Injury to the perforating branch of the peroneal artery has not been reported previously as a cause of acute compartment syndrome following soft-tissue injury to the ankle. We describe the case of a 23-year-old male who sustained such an injury resulting in an acute compartment syndrome. In a review of the literature, we could find only five previous cases, all of which gave rise to a false aneurysm which was detected after the acute event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…58 Only five previous cases similar to this have been reported. The study concluded that compartment syndrome may develop after an ankle sprain, probably due to a tear of the peroneus longus muscle or an injury to the peroneal artery.…”
Section: Acute Ankle Sprainsupporting
confidence: 55%
“…58 Only five previous cases similar to this have been reported. The study concluded that compartment syndrome may develop after an ankle sprain, probably due to a tear of the peroneus longus muscle or an injury to the peroneal artery.…”
Section: Acute Ankle Sprainsupporting
confidence: 55%
“…1,37 The PBPA then arises within the flexor hallucis longus muscle and pierces the interosseous membrane between the tibia and fibula above the tibiofibular syndesmosis. 46 After its emergence into the extensor compartment, the PBPA gives a relatively constant skin perforator which supplies a large area on the lateral aspect of the distal one third of the leg 1 The PBPA then descends ante rior to the lateral malleolus to be distributed to the anterolateral part of the ankle and the tarsal region. 44 The anastomosis of the PBPA and the lateral malleolar branch of the ante rior tibial artery create the malleolar anastomosis.…”
Section: Anatomymentioning
confidence: 99%
“… 9 In this case and in another two reports, the perforating branch of the peroneal artery can also fall victim to an inversion of the ankle and cause acute anterior compartment syndrome of the lower leg. 3,4 In some cases, definite causes cannot be identified. Maurel et al and Creighton et al reported cases with acute compartment syndrome of the foot and acute lateral compartment syndrome of the lower leg, respectively, after ankle sprain without identifiable causative pathology, except for intracompartmental swelling.…”
Section: Discussionmentioning
confidence: 99%